Comparative protective effects of recombinant DNA and Mycobacterium bovis bacille Calmette–Guérin vaccines against M. avium infection - Martin, E (Blackwell Science Inc, 2001)
A range of strategies are being explored to develop more effective vaccines against mycobacterial infection, including immunization with DNA plasmids encoding single mycobacterial bacterial genes and the use of recombinant live vectors based on the current vaccine, Mycobacterium bovis bacille Calmette–Guérin (BCG). We have compared these two approaches using a model of virulent M. avium infection, and the gene for the immunodominant 35 kDa protein which is shared by M. avium and M. leprae, but absent from BCG. Recombinant BCG over-expressing the M. avium 35 kDa protein (BCG-35) induced strong antigen-specific proliferative and interferon-γ (IFN-γ)-secreting T cell responses. These were comparable to those induced by a single immunization with a plasmid expressing the same antigen (DNA-35); however, repeat DNA-35 immunization evoked the strongest IFN-γ release. Immunization with BCG-35 significantly reduced the growth of virulent M. avium, although this effect was similar to that induced by wild-type BCG. Immunization with DNA-35 resulted in significantly greater (2 × log(10)) reduction in the growth of M. avium. Prime-boost strategies combining DNA-35 and BCG-35 increased the protective effect above that achieved by BCG-35, but they were not more protective than DNA-35 alone. Therefore, recombinant BCG-35 and BCG induced similar levels of protection in this model, and maximal protection against M. avium infection was attained by immunization with DNA encoding the 35 kDa protein.